The upregulation of Na+,K(+)-ATPase pump numbers in lymphocytes from the first-degree unaffected relatives of patients with manic depressive psychosis in response to in vitro lithium and sodium ethacrynate. - Antia, I; Smith, C; Wood, A; Aronson, J (1995)
Patients with manic depressive disorder (DSM-III-R bipolar disorder) have an abnormality of the Na+,K(+)-ATPase pumps in their lymphocytes: the pump numbers do not upregulate to stimulation with lithium and ethacrynate. We have now investigated the in vitro adaptive responses of lymphocyte Na+,K(+)-ATPase pumps in the first-degree unaffected relatives of patients with a clear history of manic depressive disorder. The lymphocytes of the healthy relatives upregulated their Na+,K(+)-ATPase pumps normally, suggesting that the abnormal response that we have previously observed in patients with the disorder reflects a complex relation between the biochemical phenotype and the development of clinical symptoms.